Adsorption Efficiency of Polyvinyl Alcohol -Alginate Beads on Cr (VI): Effect of pH and Temperature - Te Chuan, Lee; A.N, Aizat Ahmad; N.A.S, Mohd Pu'ad; N, Manap; H.Z, Abdullah; M.I, Idris (International Journal of Integrated Engineering, 2019)
Chromium pollution has been an increasing worldwide concern because of its high toxicity and carcinogenic properties, in which requires efficient purification technique. In the present study, adsorbent beads containing polyvinyl alcohol (PVA) and sodium alginate were prepared by crosslinked with boric acid and calcium chloride for hexavalent chromium [Cr (VI)] removal. The adsorption experiments were carried out using batch adsorption studies at various solution pH and temperatures. The results demonstrated that the optimised solution pH and temperature were observed at 1 and 70 ?C, respectively. The adsorption efficiency was extremely fast and Cr (VI) was completed to be adsorbed within 45 minutes. Consequently, these results implied that the PVA-alginate beads could be considered as a potential adsorbent for Cr (VI) removal in wastewater treatment industry.